2014
DOI: 10.1103/physrevlett.113.072001
|View full text |Cite
|
Sign up to set email alerts
|

Additional Strange Hadrons from QCD Thermodynamics and Strangeness Freezeout in Heavy Ion Collisions

Abstract: We compare lattice QCD results for appropriate combinations of net strangeness fluctuations and their correlations with net baryon number fluctuations with predictions from two hadron resonance gas (HRG) models having different strange hadron content. The conventionally used HRG model based on experimentally established strange hadrons fails to describe the lattice QCD results in the hadronic phase close to the QCD crossover. Supplementing the conventional HRG with additional, experimentally uncharted strange … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
234
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(250 citation statements)
references
References 44 publications
(58 reference statements)
16
234
0
Order By: Relevance
“…In accordance with the analysis of the chiral transition temperature, T c (154±9) MeV [4], bulk thermodynamic observables change smoothly in the transition region. At low temperature they are found to be in quite good agreement with hadron resonance gas (HRG) model calculations, although some systematic deviations have been observed, which may be attributed to the existence of additional resonances which are not taken into account in HRG model calculations based on well established resonances listed in the particle data tables [5,6].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…In accordance with the analysis of the chiral transition temperature, T c (154±9) MeV [4], bulk thermodynamic observables change smoothly in the transition region. At low temperature they are found to be in quite good agreement with hadron resonance gas (HRG) model calculations, although some systematic deviations have been observed, which may be attributed to the existence of additional resonances which are not taken into account in HRG model calculations based on well established resonances listed in the particle data tables [5,6].…”
supporting
confidence: 62%
“…We therefore compare the QCD results also with a HRG model that includes additional strange baryons,which are not listed in the PDG but are predicted in quark models and lattice QCD calculations. We successfully used such an extended HRG model (QM-HRG) in previous calculations [5,6]. As can be seen in Fig.…”
Section: A Pressure and Net Baryon-number Densitymentioning
confidence: 81%
“…The strangeness sector is especially interesting in light of the p/π puzzle at the LHC [85] where it has been suggested that there are possibly missing strange resonances when compared to Lattice QCD [86,87] and/or there could be a flavor hierarchy of chemical freeze-out temperatures [36,88]. Recent work [89] has also looked into the dynamics of strangeness and found that strange hadrons (with the exception of Λ's) generally freeze-out sooner than light hadrons.…”
Section: Strangeness Sectormentioning
confidence: 99%
“…The hadronic phase of the QCD medium is successfully addressed also by the Hadron Resonance Gas (HRG) Model [10][11][12], in statistical thermodynamic framework. An ideal HRG, formulated with discrete mass spectrum of * Electronic address: prem@vecc.gov.in identified hadrons and resonances, has been reinforced with the ab-initio confirmation [13][14][15][16] from the LQCD. Also, as yet unmeasured higher-mass hadron states, provided by the exponentially growing continuum mass spectrum, proposed [17] by R. Hagedorn, have important contribution to the equation of state (EoS) [18][19][20] below the critical temperature (T c ) for the QCD change of phase.…”
Section: Introductionmentioning
confidence: 99%